Pharmaceutical characterization of novel tenofovir liposomal formulations for enhanced oral drug delivery: in vitro pharmaceutics and Caco-2 permeability investigations - Spinks CB; Zidan AS; Khan MA; Habib MJ; Faustino PJ (Dove Medical Press, 2017)
Crystal B Spinks,1 Ahmed S Zidan,2,3 Mansoor A Khan,4 Muhammad J Habib,1 Patrick J Faustino2 1Department of Pharmaceutical Sciences, School of Pharmacy, Howard University, Washington, DC, 2Division of Product Quality Research, Office of Pharmaceutical Quality, Food and Drug Administration, Silver Spring, MD, USA; 3Faculty of Pharmacy, Zagazig University, Zagazig, Egypt; 4Irma Lerma Rangel College of Pharmacy, Texas A&M Health Science Center, College Station, TX, USA Abstract: Tenofovir, currently marketed as the prodrug tenofovir disoproxil fumarate, is used clinically to treat patients with HIV/AIDS. The oral bioavailability of tenofovir is relatively low, limiting its clinical effectiveness. Encapsulation of tenofovir within modified long-circulating liposomes would deliver this hydrophilic anti-HIV drug to the reticuloendothelial system for better therapeutic efficacy. The objectives of the current study were to prepare and pharmaceutically characterize model liposomal tenofovir formulations in an attempt to improve their bioavailability. The entrapment process was performed using film hydration method, and the formulations were characterized in terms of encapsulation efficiency and Caco-2 permeability. An efficient reverse-phase high-performance liquid chromatography method was developed and validated for tenofovir quantitation in both in vitro liposomal formulations and Caco-2 permeability samples. Separation was achieved isocratically on a Waters Symmetry C8 column using 10 mM Na2PO4/acetonitrile pH 7.4 (95:5 v/v). The flow rate was 1 mL/min with a 12 min elution time. Injection volume was 10 µL with ultraviolet detection at 270 nm. The method was validated according to United States Pharmacopeial Convention category I requirements. The obtained result showed that tenofovir encapsulation within the prepared liposomes was dependent on the employed amount of the positive charge-imparting agent. The obtained results indicated that calibration curves were linear with r2 > 0.9995 over the analytical range of 1–10 µg/mL. Inter- and intraday accuracy and precision values ranged from 95% to 101% and 0.3% to 2.6%, respectively. The method was determined to be specific and robust. Regarding the potential of the prepared vectors to potentiate tenofovir permeability through the Caco-2 model, a 10-fold increase in tenofovir apparent permeability was observed compared to its oral solution. In conclusion, this novel and validated method was successfully applied to characterize both in vitro encapsulation efficiency and Caco-2 permeability transport for the pharmaceutical assessment of novel tenofovir formulations. Keywords: liposomes, tenofovir, targeting, chromatography, entrapment, permeation